Rancang Bangun Sistem Informasi Administrasi Akademik Siswa Berbasis Web (Studi Kasus : SMA Al-Mahadul Islam YAPI) - Abidin, Ali Zainal; Lusiani, Titik; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
Student administration academic information system on web based can provide periodic reports of students online activity, whether it be information on grades, attendance, and scores of students who are concerned violations. Yapi is one institution that requires the dormitory system to each student who was educated there. Along with the increased number of students from year to year, Yapi has difficulty in terms of making periodic reports of students. One solution of the problem is the construction of an student administration academic information system that can help Yapi in the process of making periodic reports of students. This system was built on web based using HTML programming language, PHP and Javascript and uses MySQL for the database. This application can help the academics functions in terms of student data storage until the making of periodic reports for students and their parents. This system was built as a means of improving the quality of education in schools as well as easy solutions for the Yapi This system can perform maintenance and management of process data into useful information in making the report periodic students. This system can provide information to the parents of periodic progress reports her son and daughter.   Keywords : YAPI, Academic Information System, PHP